Evaluation of counting error due to colony masking in bioaerosol sampling. - Chang, C W (1994)
Colony counting error due to indistinguishable colony overlap (i.e., masking) was evaluated theoretically and experimentally. A theoretical model to predict colony masking was used to determine colony counting efficiency by Monte Carlo computer simulation of microorganism collection and development into CFU. The computer simulation was verified experimentally by collecting aerosolized Bacillus subtilis spores and examining micro- and macroscopic colonies. Colony counting efficiency decreased (i) with increasing density of collected culturable microorganisms, (ii) with increasing colony size, and (iii) with decreasing ability of an observation system to distinguish adjacent colonies as separate units. Counting efficiency for 2-mm colonies, at optimal resolution, decreased from 98 to 85% when colony density increased from 1 to 10 microorganisms cm-2, in contrast to an efficiency decrease from 90 to 45% for 5-mm colonies. No statistically significant difference (alpha = 0.05) between experimental and theoretical results was found when colony shape was used to estimate the number of individual colonies in a CFU. Experimental colony counts were 1.2 times simulation estimates when colony shape was not considered, because of nonuniformity of actual colony size and the better discrimination ability of the human eye relative to the model. Colony surface densities associated with high counting accuracy were compared with recommended upper plate count limits and found to depend on colony size and an observation system's ability to identify overlapped colonies. Correction factors were developed to estimate the actual number of collected microorganisms from observed colony counts.(ABSTRACT TRUNCATED AT 250 WORDS)